Remição da pena pela leitura: um estudo de caso da Penitenciária Juiz Plácido de Souza em Caruaru (Pernambuco). - Mendes, Clóvis Lima Bezerra (2023)
This research is based on an interest in the crisis experienced in the Brazilian penitentiary system, which is marked by prison overcrowding, the poor conditions of its prisons and the unsurprising difficulty of re-socializing prisoners. In the municipality of Caruaru (PE), the Juiz Plácido de Souza Penitentiary (PJPS) houses more than 1,600 prisoners, almost five times the initial capacity for which it was built. And, although it is also immersed in this context of crisis, the prison unit deserves to be highlighted for the program that has been sheltering for some years of education through the remission of the penalty for reading. Thus, based on a documental analysis conducted in the PJPS, this research is based on the following questions: How is the remission of sentence by reading used in the prison environment? Can this penalty redemption mechanism be applied along with the educational method developed by Paulo Freire? To this end, an analysis of the reviews of the books read by prisoners to redeem their sentence was carried out, and part of the PJPS bibliographic collection was also cataloged, in particular the books used for the purpose of redeeming the sentence through reading. It is, therefore, a qualitative field research, in which, from a case study (the PJPS reading referral program), a documental study was carried out with the objective of analyzing how reading can contribute for a change in the lives of prisoners, as well as whether through it is possible to influence the formation of subjects of law in the prison environment, in which incarcerated citizens identify themselves as social actors. In addition, an analysis of the bibliography used and made available was also carried out.